El trabajo de los niños , niñas y adolescentes y su vulneración de los derechos fundamentales - Laine Zambrano, Divina Caridad (2013)
The present thesis on the theme: "The work of children and adolescents and their violation of fundamental rights” consists of six chapters which describe relevant aspects of the topic under investigation. The introduction provides an analysis of the work of children and adolescents which violates fundamental rights of children and adolescents , focusing on the critical work of children and adolescents and the problems it causes in children and adolescents , describes the general and specific objectives, hypothesis, independent and dependent variables and resources are detailed . The theoretical framework, which consists of background research, foundation , doctrine , jurisprudence, law and comparative law in relation to the work of children and adolescents and their violation of the rights of children/as. In the methodology , details the methods used, the research design, population and sample that were used to perform the field work, surveys, techniques and tools of research, the validity of the instruments and techniques used to processing and data analysis. It is made legal reform proposal increasing a numeral to art. 95 of the Code of Children and Adolescents, in order to define the deprivation of liberty the employer to incorporate children into your template to work, finally conclusions and recommendations are detailed. Conclusions: The work of children and adolescents does not allow the harmonious development of children and adolescents and stops attending classes in educational establishments. There is no effective state control of labor activities of children and adolescents